AYAT-AYAT TASYBĪH DALAM KITAB LAṬĀ’IF AL-ISYĀRĀT - Naryono Naryono (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2019)
This study examines the verses of tasybīh according to ‘Abd al-Karīm al-Qusyairī such as ‘Arsy Allāh, Yad Allāh, and Wajh Allāh. The question that will be discussed is how al-Qusyairī interprets the verses of tasybīh in Laṭā’if al-Isyārāt. To get maximum results, the authors use descriptive-analytical methods, data are collected and compiled then analyzed. The primary source in this study is Laṭā’if al-Isyārāt, by ‘Abd al-Karīm al-Qusyairī. The secondary sources are the books of al-Qusyairī such as Risālah al-Qusyairīyah, Tartib al-Sulūk, Arba’ Rasā’il fī al-Taṣawuf. The results of this study indicate that 'Arsy according to al-Qusyairī is divided into two, namely: 'Arsy al-Samā' (where Allah resides) and 'Arsy Rahmān ('Arsy earth) located in the hearts of the ahl al-Tauhid (people those who insult Allah), whereas for the words Yad Allāh, and Wajh Allāh are ordained with the power held by Allah.